2014
DOI: 10.1038/sc.2014.178
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and antioxidative parameters in patients with spinal cord injury: implications in the pathogenesis of disease

Abstract: Study design: Oxygen-derived free radicals have been implicated in the pathogenesis of spinal cord injury (SCI) after trauma. Objective: In this review we will elucidate the importance of oxidative stress and antioxidants and its possible relationship with SCI. Methods: Literature analysis of oxidative stress, antioxidative parameters based on its implications in the pathogenesis along with devastating effect of oxidative stress parameters on SCI patients and its suggested proposed treatment by antioxidants ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
77
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 34 publications
3
77
0
Order By: Relevance
“…Cord blood stem cells promote the synthesis of MBP and proteolipid protein in the injured areas, thereby facilitating the process of remyelination (Dasari et al., 2009). Conversely, a large number of experimental evidences support oxidative stress as important mediators of secondary cell death after SCI (Cuzzocrea and Genovese, 2008; Jia et al., 2012; Fatima et al., 2015). It has been shown that administration of MO extract has powerful antioxidant effects which are probably exerted through the rosmarinic acid and the benzodioxole present in the extract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cord blood stem cells promote the synthesis of MBP and proteolipid protein in the injured areas, thereby facilitating the process of remyelination (Dasari et al., 2009). Conversely, a large number of experimental evidences support oxidative stress as important mediators of secondary cell death after SCI (Cuzzocrea and Genovese, 2008; Jia et al., 2012; Fatima et al., 2015). It has been shown that administration of MO extract has powerful antioxidant effects which are probably exerted through the rosmarinic acid and the benzodioxole present in the extract.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the secondary process includes the cascades of cellular and biological disruptions which can lead to long-term spinal deficits (Dasari et al., 2014). Increased oxidative stress (Fatima et al., 2015), redox transcription factors activity as well as elevated expression of inflammatory mediators play important roles (Popovich and Jones, 2003) in the promotion of the secondary process after the initial injury. SCI results in structural deformation such as degeneration of axons, disruption of neural tissue, neural and glial cell death, and demyelination around the lesion site.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the neurons in the CNS are vulnerable to oxidative damage due to the low antioxidant ability and limited scope for up-regulation when the oxidative stress is enhanced [6]. The above descriptions indicate that oxidative stress is a promising therapeutic target for SCI treatments [7].…”
Section: Introductionmentioning
confidence: 99%
“…There are studies indicating an imbalance between oxidants and antioxidants in patients with FMS. [7][8][9][10] The results are controversial. To the best of our knowledge, no report related to thiol/disulphide homeostasis in FMS has been published.…”
mentioning
confidence: 99%